New Acid Combination for a Successful Sandstone Acidizing - Shafiq, M.; Mahmud, H.; Rezaee, M. Reza (2017)
With the development of new enhanced oil recovery techniques, sandstone acidizing has been introduced and played a pivotal role in the petroleum industry. Different acid combinations have been applied, which react with the formation, dissolve the soluble particles; thus increase the production of hydrocarbons. To solve the problems which occurred using current preflush sandstone acidizing technology (hydrochloric acid); a new acid combination has been developed. Core flooding experiments on sandstone core samples with dimensions 1.5 in. × 3 in. were conducted at a flow rate of 2 cm 3 /min. A series of hydrochloric-acetic acid mixtures with different ratios were tested under 150°F temperature. The core flooding experiments performed are aimed to dissolve carbonate, sodium, potassium and calcium particles from the core samples. These experiments are followed by few important tests which include, porosity-permeability, pH value, Inductively Coupled Plasma (ICP) analysis and Nuclear Magnetic Resonance (NMR measurements). All the results are compared with the results of conventional hydrochloric acid technology. NMR and porosity analysis concluded that the new acid combination is more effective in creating fresh pore spaces and thus increasing the reservoir permeability. It can be seen from the pore distribution before and after the acidizing. Prior applying acid; the large size of pores appears most frequently in the pore distribution while with the applied acid, it was found that the small pore size is most the predominant of the pore distribution. These results are validated using ICP analysis which shows the effective removal of calcium and other positive ions from the core sample. This study concludes that the combination of acetic-hydrochloric acid can be a potential candidate for the preflush stage of sandstone acidizing at high temperature reservoirs.